The Concept of "Secondary Provenance": Re-interpreting Ac ko mok ki's Map as Evolving Text - Nordland, Lori Podolsky (Archivaria, 2004)
The new concept of "secondary provenance" is examined through a case study of Ac ko mok ki's map, one of the most famous from the collection of the Hudson's Bay Company Archives. This map is reinterpreted as an evolving text rather than as an objective record. In deconstructing this map, new possibilities of interpretation arise in order to better understand the map and its provenance. These interpretations are also affected by the impact of "transmedia shifts" on the provenance of the record as this map has been reproduced in books and digitized on the Internet. As the map experiences a shift from one technology to another, its provenance acquires another layer -- a "secondary provenance." RÉSUMÉ Le concept nouveau de "provenance secondaire" est examiné par l'étude de la carte Ac ko mok ki, une des plus célèbres de la collection des Archives de la Compagnie de la Baie d'Hudson. Cette carte est réinterprétée comme un texte en évolution plutôt que comme un document objectif. En déconstruisant cette carte, de nouvelles possibilités d'interprétation s'offrent afin de mieux comprendre la carte ainsi que sa provenance. Ces interprétations sont aussi touchées par l'impact de la transformation des supports sur la provenance du document, puisque la carte a été reproduite dans des livres et numérisée sur Internet. Alors que la carte passait d'une technologie à l'autre, sa provenance acquérait un autre niveau, une "provenance secondaire".